2019
DOI: 10.1177/2050640619883566
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of biologic agents and tofacitinib in moderate‐to‐severe ulcerative colitis: A systematic overview of meta‐analyses

Abstract: Background: Ulcerative colitis (UC) is an inflammatory disease of the colon and rectum. Treatment options include biologics and tofacitinib. Objectives: We aim to summarize the evidence on efficacy and safety of biologics and tofacitinib in moderate-to-severe UC. Methods: PubMed, Embase, Scopus, and the Cochrane Library were systematically searched to identify meta-analyses of randomized controlled trials assessing adalimumab, golimumab, infliximab, vedolizumab, and tofacitinib in UC. Efficacy outcomes include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
2
16
0
4
Order By: Relevance
“…Encouragingly, the HRQoL of patients did not differ significantly between those on conventional therapy, which tend to have milder symptoms, reflecting the authors' belief regarding the effectiveness of biologics in patients with IBD 1 . The authors also found differences in the effect of different biologics on HRQoL similar to other studies [47][48][49][50][51] , which needs further investigation to guide future treatment strategies. This includes whether any therapeutic drug monitoring (TDM) takes place as under-dosing impacts on their effectiveness in practice [52][53][54][55] .…”
supporting
confidence: 79%
“…Encouragingly, the HRQoL of patients did not differ significantly between those on conventional therapy, which tend to have milder symptoms, reflecting the authors' belief regarding the effectiveness of biologics in patients with IBD 1 . The authors also found differences in the effect of different biologics on HRQoL similar to other studies [47][48][49][50][51] , which needs further investigation to guide future treatment strategies. This includes whether any therapeutic drug monitoring (TDM) takes place as under-dosing impacts on their effectiveness in practice [52][53][54][55] .…”
supporting
confidence: 79%
“…Therefore, it is correct to state that the assessment of the degree of disease activity cannot disregard the recognition, topographical description, and possible presence in the glandular (crypt abscess) of neutrophilic granulocytes, and that expressions such as “IBD in the quiescent phase” of mild/moderate disease activity may actually increase the diagnostic confusion that revolves around the concept of mucosal healing [ 21 , 23 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several molecules have been developed and approved for the treatment of IBD patients, but the disease remission rate still remains modest, highlighting the real need for new drugs and for alternative development strategies [30]. IBD clinical trials are increasingly complex and sophisticated, involving new outcomes (e.g., patient-reported outcomes, biomarkers, and histological healing), central reading, and re-randomization [31].…”
Section: Discussionmentioning
confidence: 99%